THE BLOOD PRESSURE AND THERAPY EXPENDITURE CHANGE DUE TO HYPERTENSION COMORBIDITY: AN ANALYTICAL PROSPECTIVE STUDY IN SECONDARY CARE HOSPITALS IN JOGJAKARTA INDONESIA - Suhadi, Rita; Thobari, Jarir At; Irawan, Bambang; Dwiprahasto, Iwan (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To measure the comorbid effect on blood pressure and therapy expenditure in 4 secondary care hospitals in Jogjakarta. Methods: We conducted an 8-month prospective pharmacoeconomic study with hospital perspective. All hypertensive outpatients, with Askes-insurance whose beneficiaries were governmental employees, with at least 2 moly visits at the index date were included. The subjects with malignancy, hemodialysis, and less than 4 visits were excluded. The expenditure comprised the cost for cardiovascular medicine, doctor, physical/laboratory test, emergency visit, and physiotherapy. We analyzed the expenditure change and sensitivity analysis with Anova-test, whereas the proportion of subjects with good controlled blood pressure with the chi-square test. Results: The eligible subjects (N=656) consisted of no comorbid (n=105), stroke (n=82), cardiovascular (n=209), diabetes mellitus/chronic kidney disease or DM/CKD (n=149), and combined comorbid (n=111) groups. The baseline blood pressure was similar to no comorbid (p>0.05), except for the diastolic blood pressure in a cardiovascular group. The stroke and cardiovascular groups had more subjects at mean systolic blood pressure lower than 140 mmHg with odds ratio (OR) 2.01 (CI95%:1.12-3.62) and 2.10 (CI95%:1.31-3.39) respectively than no comorbid group; but the mean blood pressure was not clinically different. The total therapy expenditure increased at 6.5% (p<0.61); 22.7% (p<0.03); 78.6% (p<0.01); 78.5% (p<0.01) per subject-visit for stroke, cardiovascular, DM/CKD, and combined-comorbid groups than no comorbid group respectively. Except for stroke group, the incremental expenditure was price-sensitive (p<0.05). Conclusion: The total therapy expenditure but not blood pressure was likely to be influenced by hypertension comorbidity. We suggest that preventing hypertension comorbidity has the benefit to reduce total therapy expenditure.